Dopaminergic gene-epigenetic interactions and impulsivity traits in elite combat sport athletes - Reclaw, R.; Chmielowiec, J.; Chmielowiec, K.; Masiak, J.; Grzywack, A. (Frontiers in Psychology, 2026)
Dopaminergic signaling is a key mechanism underlying behavioral regulation and impulse control. While epigenetic variation in dopaminergic genes has been linked to dysregulated behavior in clinical populations, its relevance in high-functioning individuals remains less clear. Elite combat sport athletes provide an informative model for studying self-control in performance-demanding environments. This study examined differences between combat sport athletes and matched controls in DAT1 (SLC6A3) promoter methylation, DRD2 rs1076560 genotype, and trait impulsivity, and tested whether DRD2 variation moderates methylation patterns. A total of 209 males (n=100 athletes; n=109 controls) were included. Methylation across 33 CpG sites in the DAT1 promoter was quantified from whole-blood DNA, DRD2 rs1076560 was genotyped using real-time PCR, and impulsivity was assessed with the Barratt Impulsiveness Scale (BIS-11). Athletes showed higher DAT1 methylation (Z=7.022, p<0.0001) and lower impulsivity across BIS-11 domains (all p<0.01) than controls. A significant group × genotype interaction was observed for DAT1 methylation (F1,204=14.05, p=0.0002), with A allele carriers showing the highest methylation among athletes. No direct genotype effect on impulsivity was found. These results suggest experience-related dopaminergic epigenetic differences among elite athletes, potentially shaped by genetic background, and support integrative models of self-regulation in high-performance contexts. Such biomarkers may help inform individualized approaches to psychological training and performance resilience.